Newspaper Advertising As A Source For The History Of Kazan Industry In The Second Half Of The Xix Century - Galanin, Sergey (2018)
According to the advertising data, the production may be judged by goods at the market. It’s difficult to make sharp separation between industrial and commercial establishments.The research is based on combination of quantitative methods allowing considering newspaper advertising as a specific kind of mass historic source and qualitative approach to observation of individual advertising materials. There were formal features pointed out of quantitative approach allowing to joint separate advertising materials in groups for discovering regularity. The method of comparing newspaper advertising with data from other types of historical sources was widely used, first of all information about the statistics of that period, journalism and the source of anthropogenesis and fiction book. The percentage of manufacturers among advertisers is small - about a fifth of the total.The second half of the XIX century is the time of domination of small-scale production in the Volga region. A craft successfully coexisting with the developing factory industry was still playing an important role. Craft stalls, widely oriented to the production of consumer goods, had the opportunity to respond to any changes in market conditions flexibly. Newspaper advertising was one of such methods of the reaction and reflected the peculiarities of the enterprise's behavior on the market. The vast majority of newspaper advertising manufacturers are announcement of craft enterprises. Small-scale producers used to carry out retail sales themselves. According to newspaper advertising, one can judge not only about trade, but also about the development of a number of industries.Approaches to the marketing of small industrial enterprises can be used in the modern practice of industrial entrepreneurship. Newspaper advertising is in many ways a unique source that characterizes Russian business practices